Microsoft Visual Basic 2008 for Windows, mobile, web, and office applications complete - Shelly, Gary B.; Hoisington, Corinne (Shelly Cashman series, 2009)
Microsoft Visual Basic 2008 for Windows, Mobile, Web, and Office Applications: Complete teaches students the essentials of computer programming using the latest Visual Basic programming language, Visual Basic 2008. Nine chapters and four appendices cover topics such as designing a Visual Basic user interface, creating a windows application, variables and arithmetic operations, mobile applications using decision structures, loop structures, Visual Studio tools for Office applications, and function procedures and exception handling. Written in a straight-forward style with the innovative Guided Program Development section in each chapter, this text makes it easy for any novice programmer to understand the core capabilities and fundamental skills and techniques for Visual Basic 2008.